Evaluation of thromboembolic event, basic coagulation parameters, and associated factors in patients with colorectal cancer: a multicenter study - Admasu, Fitalew Tadele; Dejenie, Tadesse Asmamaw; Ayehu, Gashaw Walle; Zewde, Edget Abebe; Dessie, Gashaw; Adugna, Dagnew Getnet; Enyew, Engidaw Fentahun; Geto, Zeleke; Abebe, Endeshaw Chekol (Frontiers in Oncology, 2023)
Background: Patients with colorectal cancer are at an increased risk of hemostatic disturbances, and recent studies have shown that coagulation disorders could be the first sign of malignancy. Although coagulopathy is a significant cause of cancer-related death and disability, it is usually underestimated, and there has been no recent scientific evidence regarding the exact burden and its specific determinants. Moreover, the public health importance of the risk of coagulopathy among patients with colorectal polyps has not been addressed. Material and Methods: An institution-based comparative cross-sectional study was conducted on a total of 500 study participants (250 colorectal cancer, 150 colorectal polyp, and 100 control groups) from January to December 2022. Venous blood was collected for basic coagulation and platelet analysis. Descriptive statistics and non-parametric tests (Kruskal-Wallis and Dunn-Bonferroni pairwise comparisons) were used to compare study parameters among the groups. The test results expressed as medians and interquartile ranges. Binary logistic regressions were fitted, and statistical significance was declared at P-value of less than 0.05, with 95% CI. Results: The prevalence of coagulopathy among colorectal cancer patients was 198 (79.2%; 95% CI: 73.86, 83.64), while the prevalence was 76 (50.7%; 95% CI: 45.66, 54.34) among colorectal polyp patients. From the final model, age between 61-70(AOR= 3.13: 95% CI: 1.03, 6.94), age > 70 years (AOR= 2.73: 95% CI: 1.08, 4.71), hypertension (AOR= 6.8: 95% CI: 1.07, 14.1), larger tumor size (AOR= 3.31: 95% CI: 1.11, 6.74), metastatic cancer (AOR= 5.8: 95% CI: 1.1, 14.7), and BMI ≥30kg/m2 (AOR= 3.8: 95% CI: 2.3, 4.8) were positively associated with coagulopathy. Conclusion: This study showed that coagulopathy is a major public health concern among patients with colorectal cancer. Therefore, existing oncology care efforts should be strengthened to prevent coagulopathy among patients with colorectal cancer. Moreover, patients with colorectal polyps should receive more attention.